Lectins in diagnostic microbiology: use of wheat germ agglutinin for laboratory identification of Neisseria gonorrhoeae. - Schaefer, R L (1979)
A lectin slide agglutination test has been developed for the confirmatory identification of Neisseria gonorrhoeae. With wheat germ lectin as an agglutinin, 164 of 165 clinical isolates of N. gonorrhoeae gave a 3 to 4+ reaction within 6 to 8 min. Four gonococcal isolates, even though negative by the fluoresecent-antibody method, gave strong positive reactions with the wheat germ lectin. Among 23 isolates of Neisseria meningitidis tested, which included representatives of sero-groups A, B, C,D, X, Y, and Z, only one strain in group X gave a false-positive reaction. The nonpathogenic species of Neisseria, as well as Branhamella catarrhalis, all showed negative reactions with the wheat germ agglutinin. The novel method provides a simple, rapid, and inexpensive means for the laboratory diagnosis of gonorrhea and obviates the need for performing second-stage sugar fermentation studies or utilizing the more expensive fluorescent-antibody techniques.